Process and Collaboration: Two Competitions: Monroeville Civic Center/Hong Kong Peak - Alex Krieger (Oz, 1985)
I work with a partner, Lawrence Chan. Therefore, this essay is about a thought process which is the product of a collaboration. Though no less subject to individual initiative, whimsy, and trail and error, working in partnership demands common purposes…